ZENTRALAFRIKA: MUSIKGESCHICHTE IN BILDERN, by Jos Gansemans and Barbara Schmidt-Wrenger, VEB Deutscher Verlag fur Musik, Leipzig, 1986, Band I, Musikethnologie, Lieferung 9, 210 pages, 238 pictures (partly in colour), map, musical transcriptions and other text illustrations, ISBN 3-370-00150-0. - Kubik, Gerhard (International Library of African Music, 1996)
pages: 132-129
Keywords: African Music